Problem zawierania powtórnych małżeństw w piśmiennictwie łacińskich Ojców Kościoła żyjących na przełomie IV i V wieku aż do czasów św. Augustyna - Dzierżon, Ginter (Ius Matrimoniale, 2016)
The author of the article presented the views of Latin Church Fathers from the turn of the 5th century on the question of the possibility of contracting another marriage. His analyses showed that they were against such practices. The popes of those times, Innocent I and Gregory the Great, made a few particular decisions in that matter connected with the specific conditions in which Christians lived at that time, namely the relation between the Christian doctrine and the then valid Roman law. The author also proved that, as far as marriage was concerned, the Church Fathers implicitly acknowledged secular jurisdiction apart from the regulations that were non-acceptable from the perspective of the Christian doctrine.